SEMIOTICS ANALYSIS OF RUANGGURU ADVERTISING IN TELEVISION MEDIA - Al Mutia Gandhi (Universitas Lambung Mangkurat, 2020)
RuangGuru is one of the most successful startups in Indonesia, which is engaged in online tutoring. The application user has reached up to 15 million students. This achievement is the result of the advertisements that often appear on television media, especially during new school academic year or new semester. This study examines advertisements on television media less than 30 seconds to attract customers. This study uses semiotic to analyze television ads for the product. The research method uses an interpretive descriptive approach to analyze the signs used in advertisements. The data resource is four video recording advertisements on television media. The analysis starts with transcription and making video screenshots to sharpen the analysis. The results indicate that to attract television viewers, RuangGuru uses signs that indicate superior features. The features such as animated learning videos, practice questions, discussion, and ease of learning through applications. The celebrity figures in the advertisement represent students and parents who will later become consumers of RuangGuru. The ad also has a sign indicating how easy it is to pay and how cheap it is to subscribe to the Ruang Guru application compared to conventional tutoring. The blue color, which is the dominance of advertisements, shows that the RuangGuru app is trustworthy and can increase students' confidence in facing classroom learning.